Preoperative chemoradiotherapy and postoperative chemotherapy with fluorouracil and oxaliplatin versus fluorouracil alone in locally advanced rectal cancer: initial results of the German CAO/ARO/AIO-04 randomised phase 3 trial - Roedel, Claus; Liersch, Torsten; Becker, Heinz; Fietkau, Rainer; Hohenberger, Werner; Hothorn, Torsten; Graeven, Ullrich; Arnold, Dirk; Lang-Welzenbach, Marga; Raab, Hans-Rudolf; Suelberg, Heiko; Wittekind, Christian; et al. (Lancet Oncology, 2012)
BACKGROUND: Preoperative chemoradiotherapy, total mesorectal excision surgery, and adjuvant chemotherapy with fluorouracil is the standard combined modality treatment for rectal cancer. With the aim of improving disease-free survival (DFS), this phase 3 study (CAO/ARO/AIO-04) integrated oxaliplatin into standard treatment. METHODS: This was a multicentre, open-label, randomised, phase 3 study in patients with histologically proven carcinoma of the rectum with clinically staged T3-4 or any node-positive disease. Between July 25, 2006, and Feb 26, 2010, patients were randomly assigned to two groups: a control group receiving standard fluorouracil-based combined modality treatment, consisting of preoperative radiotherapy of 50·4 Gy plus infusional fluorouracil (1000 mg/m(2) days 1-5 and 29-33), followed by surgery and four cycles of bolus fluorouracil (500 mg/m(2) days 1-5 and 29; fluorouracil group); and an experimental group receiving preoperative radiotherapy of 50·4 Gy plus infusional fluorouracil (250 mg/m(2) days 1-14 and 22-35) and oxaliplatin (50 mg/m(2) days 1, 8, 22, and 29), followed by surgery and eight cycles of adjuvant chemotherapy with oxaliplatin (100 mg/m(2) days 1 and 15), leucovorin (400 mg/m(2) days 1 and 15), and infusional fluorouracil (2400 mg/m(2) days 1-2 and 15-16; fluorouracil plus oxaliplatin group). Randomisation was done with computer-generated block-randomisation codes stratified by centre, clinical T category (cT1-4 vs cT4), and clinical N category (cN0 vs cN1-2) without masking. DFS is the primary endpoint. Secondary endpoints, including toxicity, compliance, and histopathological response are reported here. Safety and compliance analyses included patients as treated, efficacy endpoints were analysed according to the intention-to-treat principle. This study is registered with ClinicalTrials.gov, number NCT00349076. FINDINGS: Of the 1265 patients initially enrolled, 1236 were evaluable (613 in the fluorouracil plus oxaliplatin group and 623 in the fluorouracil group). Preoperative grade 3-4 toxic effects occurred in 140 (23%) of 606 patients who actually received fluorouracil and oxaliplatin during chemoradiotherapy and in 127 (20%) of 624 patients who actually received fluorouracil chemoradiotherapy. Grade 3-4 diarrhoea was more common in those who received fluorouracil and oxaliplatin during chemoradiotherapy than in those who received fluorouracil during chemoradiotherapy (73 patients [12%] vs 52 patients [8%]), as was grade 3-4 nausea or vomiting (23 [4%] vs nine [1%]). 516 (85%) of the 606 patients who received fluorouracil and oxaliplatin-based chemoradiotherapy had the full dose of chemotherapy, and 571 (94%) had the full dose of radiotherapy; as did 495 (79%) and 601 (96%) of 624 patients who received fluorouracil-based chemoradiotherapy, respectively. A pathological complete response was achieved in 103 (17%) of 591 patients who underwent surgery in the fluorouracil and oxaliplatin group and in 81 (13%) of 606 patients who underwent surgery in the fluorouracil group (odds ratio 1·40, 95% CI 1·02-1·92; p=0·038). In the fluorouracil and oxaliplatin group, 352 (81%) of 435 patients who began adjuvant chemotherapy completed all cycles (with or without dose reduction), as did 386 (83%) of 463 patients in the fluorouracil group. INTERPRETATION: Inclusion of oxaliplatin into modified fluorouracil-based combined modality treatment was feasible and led to more patients achieving a pathological complete response than did standard treatment. Longer follow-up is needed to assess DFS. FUNDING: German Cancer Aid (Deutsche Krebshilfe).
EVALuna2:5332